Psycho-cultural Dynamics of Mataram Javanese Shopping Orientation - Nugrohadi, Gratianus Edwi; Tulipa, Diyah; Ardhanari, Margaretha (Mediterranean Journal of Social Sciences, 2019)
Cultural diversity influences various behaviours in Indonesia. One of them is about the consumption pattern of the society. The formed ethnic identity and their interaction with other cultural groups can create new patterns of behaviour in consumption. For this reason, the scientific research on how ethnic identity and their cultural interactions affect shopping orientation is needed. This research was conducted with a qualitative approach by using a phenomenological model. The informants were chosen purposively with the main criteria: Javanese consumers that very affected by Mataram cultures. The data collection use semi-structured interview and observation models. Then, the collected data is analysed thematically with an inductive model (inductive thematic analysis) after being validated communicatively, argumentatively and ecologically. The results of this study stated that the shopping orientation of informant is utilitarian (based on the needs, benefits, and usefulness). The utilitarian shopping orientation is qualitatively influenced by intrapsychic aspects of the family, as well as the extrapsychic aspects. The intrapsychic aspects pointed out three thematic categories, namely: family background, education in the family, and value systems that are internalised in the family, while the extrapsychic aspect also pointed out three thematic categories, namely: environment (friendship, living area, and workplace), media and gender. Then, the interactive dynamics of utilitarian shopping orientation are manifested in the form of shopping behaviour at various retail formats.